2019
DOI: 10.3389/fneur.2019.00223
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multimodal Apparatus to Generate Biomechanically Reproducible Spinal Cord Injuries in Large Animals

Abstract: Rodents are widespread animal models in spinal cord injury (SCI) research. They have contributed to obtaining important information. However, some treatments only tested in rodents did not prove efficient in clinical trials. This is probably a result of significant differences in the physiology, anatomy, and complexity between humans and rodents. To bridge this gap in a better way, a few research groups use pig models for SCI. Here we report the development of an apparatus to perform biomechanically reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…We started with five farm pigs, referred to as SCI-1 to SCI-5. Our previous study showed that an impact of 46 N with our spring-loaded impactor was creating such serious tissue damage that it was likely to be beyond any repair ( Züchner et al, 2019 ). Therefore, as a first trial, we decided to reduce the strength by half.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We started with five farm pigs, referred to as SCI-1 to SCI-5. Our previous study showed that an impact of 46 N with our spring-loaded impactor was creating such serious tissue damage that it was likely to be beyond any repair ( Züchner et al, 2019 ). Therefore, as a first trial, we decided to reduce the strength by half.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we described the development of an impacting apparatus to generate SCIs in large animals ( Züchner et al, 2019 ). We demonstrated that our spring-load impactor generates graded and reproducible impacts on gel pads.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations